Raymond Aron's philosophy of political responsibility : freedom, democracy and national identity - Adair-Toteff, Christopher (Edinburgh University Press, 2019)
An illuminating account of Raymond Aron's political philosophy and its enduring relevance today Raymond Aron made major investigations into the dialectic between war and peace, and also developed a sophisticated theory of international relations. Despite this, his body of work has been overlooked compared to that of his more famous contemporaries. This book shines a light on both the man and his work on ideological critique, the philosophy of history, international relations, and political economy. The book also discusses Aron's political legacy and argues that a number of his critiques and theories can help us address many of the problems and conflicts of the 21st century.